2019
DOI: 10.1186/s12870-019-1630-4
|View full text |Cite
|
Sign up to set email alerts
|

Full-length transcript sequencing and comparative transcriptomic analysis to evaluate the contribution of osmotic and ionic stress components towards salinity tolerance in the roots of cultivated alfalfa (Medicago sativa L.)

Abstract: BackgroundAlfalfa is the most extensively cultivated forage legume. Salinity is a major environmental factor that impacts on alfalfa’s productivity. However, little is known about the molecular mechanisms underlying alfalfa responses to salinity, especially the relative contribution of the two important components of osmotic and ionic stress.ResultsIn this study, we constructed the first full-length transcriptome database for alfalfa root tips under continuous NaCl and mannitol treatments for 1, 3, 6, 12, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
103
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 61 publications
9
103
1
Order By: Relevance
“…Several transcriptome-based and proteome studies have been conducted to understand salinity stress in alfalfa [49,54,66,[81][82][83][84][85][86][87]. After a three-day salt treatment, a proteomic study on the roots of two-week-old seedlings found 83 differentially expressed proteins in alfalfa cultivars with contrasting tolerances to salinity (Table 1) [81].…”
Section: Proteome and Transcriptomic Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several transcriptome-based and proteome studies have been conducted to understand salinity stress in alfalfa [49,54,66,[81][82][83][84][85][86][87]. After a three-day salt treatment, a proteomic study on the roots of two-week-old seedlings found 83 differentially expressed proteins in alfalfa cultivars with contrasting tolerances to salinity (Table 1) [81].…”
Section: Proteome and Transcriptomic Analysesmentioning
confidence: 99%
“…Transcriptomic approaches have been employed for alfalfa to understand the gene expression associated with salt stress (Table 1) [49,66,[83][84][85]87]. Eighty-two unique transcripts were found from the salt-stressed seedlings of alfalfa by sampling at different time intervals from 10 min to 24 h, including 24% that were proteins related to plant metabolism and 9% that were related to abiotic stress [87].…”
Section: Proteome and Transcriptomic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…After PCR amplification, the BluePippin Size Selection System (Sage Science, Beverly, MA, USA) was used to select product sizes, and then three libraries were produced, corresponding to fragments of 1-2, 2-3 and 3-6 kb for each sample length. The amplified cDNA products were then subjected to the construction of SMRTbell Template libraries according to the Iso-Seq protocol [87,88]. Further, Qubit2.0 and Agilent 2100 were used to confirm accurate quantification and library size, respectively; only when the library size met the expected criteria was sequencing performed.…”
Section: Rna Isolation and Assessmentmentioning
confidence: 99%